2016
DOI: 10.1136/heartjnl-2016-310026
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy and long-term prognostic value of stress echocardiography in octogenarians

Abstract: In octogenarians, SE demonstrated excellent feasibility, safety and diagnostic accuracy. SE parameters were independent predictors of NFMI and CV events, and the presence of inducible ischaemia was associated with a 50% increase in all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…All SE studies were performed using either treadmill exercise or pharmacological (dobutamine-atropine) stress as described previously (13). As per protocol heart rate lowering medications were withheld for 48hrs prior to testing.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…All SE studies were performed using either treadmill exercise or pharmacological (dobutamine-atropine) stress as described previously (13). As per protocol heart rate lowering medications were withheld for 48hrs prior to testing.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…Few studies assessed the accuracy of exercise SE for detecting stable CAD in the elderly. The study by Gurunathan et al combined the results of patients with documented CAD that followed different exercise methods [ 39 ]. Meta-analyses of studies that included patients from all age groups reported s sensitivity of exercise SE of 79–85% and s specificity of 77–89% [ 34 , 40 , 41 , 42 , 43 ].…”
Section: Exercise Stress Echocardiography For Diagnosis Of Stable mentioning
confidence: 99%
“…Gurunathan, et al studied 374 octogenarians [30] and confirmed that ischemia was an independent predictor of events, associated with a 50% increase in all-cause mortality.…”
Section: Speckle Trackingmentioning
confidence: 99%